Persepsi Guru Sekolah Dasar terhadap Penggunaan Teknologi Berbasis Deep Learning dalam Transformasi Pembelajaran IPAS - M Choirul Muzaini; Syahrul Aziz (Jurnal Wahana Literasi Pendidikan, 2026)
This study aims to analyze elementary school teachers' perceptions of the use of deep learning-based technology in transforming science and mathematics learning at SD Negeri 2 Mataram Udik, Bandar Mataram District, Central Lampung Regency. The research uses a qualitative approach with a descriptive type, involving fourth-grade science teachers as research subjects. Data collection techniques include in-depth interviews, learning observations, and documentation, while data analysis is carried out through the stages of data reduction, data presentation, and thematic conclusion drawing. The results of the study show that teachers have a positive perception of the use of deep learning-based technology in IPAS learning. The technology is considered capable of increasing the effectiveness of learning, enriching teaching media and methods, supporting more adaptive and personalized learning, and increasing student engagement and understanding of IPAS material. The use of technology also encourages the transformation of the role of teachers into facilitators and analysts of data-based learning processes. However, there are still challenges related to improving teachers' technical competencies and technological infrastructure readiness. This study concludes that deep learning-based technology has great potential in supporting innovation and transformation of IPAS learning in elementary schools, thus requiring strengthening teacher training, school policy support, and sustainable technology integration in the learning curriculum.